(untitled) (Ustozlar uchun, 2026)
This article explores the intricate process and significant challenges inherent in movie translation, a critical component in the global dissemination of cinematic works. It delves into the multifaceted linguistic, cultural, and technical obstacles faced by translators, ranging from idiomatic expressions and humor to synchronization and subtitling constraints. The paper examines various translation strategies employed to convey the original artistic intent while ensuring cultural relevance and audience comprehension across diverse linguistic landscapes. Ultimately, effective movie translation is shown to be indispensable for fostering cross-cultural understanding and enriching the international reception of films, profoundly influencing their global impact and legacy.